The impact of bladder neck mucosal eversion during open radical prostatectomy on bladder neck stricture and urinary extravasation - Schöppler, Gita (International urology and nephrology, 2012)
Purpose: To determine whether the bladder neck mucosal eversion (BNM-eversion) during radical retropubic prostatectomy (RRP) reduces the risk of bladder neck stricture (BNS) and of peri-anastomotic extravasation (PAE) in postoperative cystography.Methods: Two hundred and eleven patients with clinically localized prostate cancer underwent RRP and were prospectively randomized into patients with BNM-eversion (group I) and without BNM-eversion (group II). All patients underwent an evaluation of PAE by retrograde cystography on postoperative day 8. We assessed BNS after 6 months.Results: Ninety-two patients with and 113 patients without BNM-eversion were included. There was no significant difference in baseline characteristics, including age, TNM-classification, Gleason score, PSA, prostate volume, and blood loss in both groups. A complete follow-up of 6 months for BNS was available for 188 patients (89.1 %). Sixteen BNS out of 188 patients were recorded, 4.7 % (n = 4) in group I and 11.7 % (n = 12) in group II (p = 0.09). Data from 205 out of 211 patients were available for the evaluation of the extravasation by cystography. Peri-anastomotic extravasation was detectable in 11.96 %, (11/205) in group I and in 21.24 % (24/205) in group II (p = 0.08).Conclusion: BNM-eversion does not have a positive influence on the prevention of bladder neck strictures. Peri-anastomotic extravasation detected by cystography does not correlate with a formation of bladder neck stricture.
Published online: 15 May 2012
Gesehen am 13.07.2018